Acetylsalicylic acid to prevent preeclampsia and its complications. State-of-the-art of risk groups - P.A. Kuznetsov; L.S. Dzhokhadze; V.V. Shamugiya; O.M. Kravtsova (РМЖ. Мать и дитя, 2022)
P.A. Kuznetsov1,2, L.S. Dzhokhadze1,2, V.V. Shamugiya3, O.M. Kravtsova1 1Pirogov Russian National Research Medical University, Moscow, Russian Federation 2Branch of the City Clinical Hospital No. 24 — Perinatal Center, Moscow, Russian Federation 3Branch of the V.V. Veresaev City Clinical Hospital, Moscow, Russian Federation This paper reviews current published data on the use of acetylsalicylic acid (ASA) for preventing preeclampsia and its complications and techniques to determine risk groups for im-plementing this preventive treatment. In addition, the authors summarize data on the history of ASA advent and introduction into medical practice (particularly obstetrics) and presumed mech-anisms of its action as first-line therapy to prevent preeclampsia. Recent review papers and guidelines addressing optimal ASA dose, treatment duration, and dosing during pregnancy in Russia and worldwide are discussed. Methods that have been studied as preventive ones for preeclampsia are briefly discussed. It was demonstrated that anamnestic determination of risk groups of early preeclampsia is not always enough. Expanded combined first-trimester screening is a perspective diagnostic tool. Success in determining high-risk groups and optimal prevention of preeclampsia may significantly affect population health by  reducing maternal and perinatal mortality and long-term risk of cardiovascular events both in the mother and child. Keywords: preeclampsia, acetylsalicylic acid, screening, placental disorders, trophoblast, fetal growth restriction, prevention of preeclampsia, uterine artery pulsatility index, pregnancy-associated plasma protein A (PAPP-A), placental growth factor (PlGF). For citation: Kuznetsov P.A., Dzhokhadze L.S., Shamugiya V.V. Acetylsalicylic acid to prevent preeclampsia and its complications. State-of-the-art of risk groups. Russian Journal of Woman and Child Health. 2022;5(1):28–34 (in Russ.). DOI: 10.32364/2618-8430-2022-5-1-28-34.